Pasal Karet UU ITE dan Peyelesaian Konflik Digital di Indonesia - Shinta Ressmy Cakra Ningrat; Soni Akhmad Nulhaqim (Epistemik Press, 2023)
The Electronic Information and Transaction Law (UU ITE) is a problem for several groups, namely activists, pro-democracy groups, academics and students. The ITE Law specifically regulates digital law in Indonesia. This research will answer how civil society groups have demanded a revision of the ITE Law since 2016. The method used in this research is descriptive qualitative. In addition, this research is based on data collected from various mass media, scientific research journals, v-dem datasets and reports from Non-Government Organizations such as SAFEnet. The results of this study conclude that the ITE Law does not resolve conflicts that occur in the online domain, but adds to existing conflicts, as evidenced by the existence of virtual politics and digital repression. The civil society movement demanding the revision of the ITE Law has had a positive impact on democracy. Meanwhile, the government that passed the ITE Law showed a trend of stagnation and a decline in democracy because it showed poor rule of law.